Biosecurity : understanding, assessing, and preventing the threat - Burnette, Ryan, 1977- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
"This book defines the concepts of biosecurity, biosafety, and biosurety and shows how they relate to one another under the overall framework of biodefense. The book also addresses biosecurity strategies for non-laboratory settings, including private sector facilities, the transportation infrastructure, and the food and agriculture sector including insurance, healthcare, the global supply chain, and agriculture. Discussions also include bioterrorism, biosecurity operations, various existing biosecurity programs, and biosecurity ethics. Designed to reach a wide variety of professionals, this resource provides a balanced and accessible look at biodefense and its applications"--
part I. An introduction to biosecurity -- part II. Elements of biosecurity -- part III. Biosecurity in various sectors -- part Ivolume Biosecurity policy, bioterrorism, and the future.
Includes index.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2015. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Biosecurity; Bioterrorism -- Prevention; Biological weapons -- Safety measures; Electronic books